2011
DOI: 10.1162/artl_a_00016
|View full text |Cite
|
Sign up to set email alerts
|

Noise and the Evolution of Neural Network Modularity

Abstract: We study the selective advantage of modularity in artificially evolved networks. Modularity abounds in complex systems in the real world. However, experimental evidence for the selective advantage of network modularity has been elusive unless it has been supported or mandated by the genetic representation. The evolutionary origin of modularity is thus still debated: whether networks are modular because of the process that created them, or the process has evolved to produce modular networks. It is commonly argu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The retina problem ( Figure 3a) is a pattern-recognition task which has been the focus of several previous studies on the evolution of modular neural network structures (Kashtan and Alon, 2005;Clune et al, 2010;Høverstad, 2011;Clune et al, 2013;Huizinga et al, 2014). In this task an 8-bit input is to be classified as 1 or 0.…”
Section: The Retina Problemmentioning
confidence: 99%
“…The retina problem ( Figure 3a) is a pattern-recognition task which has been the focus of several previous studies on the evolution of modular neural network structures (Kashtan and Alon, 2005;Clune et al, 2010;Høverstad, 2011;Clune et al, 2013;Huizinga et al, 2014). In this task an 8-bit input is to be classified as 1 or 0.…”
Section: The Retina Problemmentioning
confidence: 99%
“…Along with many ongoing theoretical explorations [2428], modularity-based partitioning has become popular recently in a broad range of applications [24,29–38]. Unlike traditional clustering methods that seek to minimize weighted combinations of the number of edges running between the modules, such as minimum cuts or normalized cuts [13], modularity-driven clustering methods compare each edge against its expected value when clustering nodes into corresponding modules.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies on evolution of modularity, the condition of MVG was mainly applied to logic circuit models with functional components such as AND, OR, and XOR [7,8,20] and to linear mapping models with inputs and outputs [6]. We followed the definition in the linear mapping model because our network model comprises a continuous dynamical system.…”
Section: E Goal Settingmentioning
confidence: 99%
“…Because networks mediate both nominal signals and noise, the link topology of a network affects its robustness to noise [17]. Several computer simulation studies have shown that robustness increases with the emergence of modular networks [18][19][20]. However, there have been few discussions regarding a mathematical framework establishing how robustness to noise can contribute to network evolution.…”
Section: Introductionmentioning
confidence: 99%